1985
DOI: 10.1177/0164027585007002005
|View full text |Cite
|
Sign up to set email alerts
|

The Ties that Bind

Abstract: This article proposes a typology of migration based on duration of annual residence in planned retirement communities. The categories of the typology-seasonal in-migrant, seasonal out-migrant, seasonal traveler, and year-round resident-are used to classify a sample of households in a southwestern retirement community. The findings suggest that out-of-state children and ties to small towns are inhibiting influences on permanent relocation after retirement. Facilitating factors associated with seasonal migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 15 publications
4
2
0
Order By: Relevance
“…They are well off financially and come to Florida primarily to enjoy the warm weather and for other recreational purposes. The characteristics of this group are generally consistent with those reported in other studies of elderly seasonal migration (e.g., Hogan and Steinnes 1998;Longino and Marshall 1990;Sullivan 1985). The stereotypical snowbird is not the only type of temporary resident in Florida, however.…”
Section: Characteristics Of Temporary Residentssupporting
confidence: 86%
See 2 more Smart Citations
“…They are well off financially and come to Florida primarily to enjoy the warm weather and for other recreational purposes. The characteristics of this group are generally consistent with those reported in other studies of elderly seasonal migration (e.g., Hogan and Steinnes 1998;Longino and Marshall 1990;Sullivan 1985). The stereotypical snowbird is not the only type of temporary resident in Florida, however.…”
Section: Characteristics Of Temporary Residentssupporting
confidence: 86%
“…The data shown in Tables 10-15 make it clear that temporary migration in Florida includes not only large numbers of non-Floridians who visit the state each year, but also large numbers of Floridians who leave the state (or travel to another location within the state) for extended periods of time. Similar patterns for ''retirement'' states have been noted before (e.g., Hogan and Steinnes 1996;McHugh et al 1995;Sullivan 1985).…”
Section: Temporary Migration Of Permanent Residentssupporting
confidence: 77%
See 1 more Smart Citation
“…Older, better-educated, healthier, metropolitan dwellers are more likely to move during the first ten years of retirement. This is consistent with the findings of other studies (Patrick, 1980;Sullivan, 1985). One study of older home owners found that those who are housing rich, but income poor, are more likely to undertake moving or nonmoving adjustment in comparison with those who are older home owners who are not in such situations.…”
Section: Household Characteristicssupporting
confidence: 91%
“…Research by White and Schollaert (1993) indicated that homeownership is among many factors that contribute to residential and neighborhood satisfaction. Using data obtained from 305 residents of moderate-to lowpriced housing from eleven counties representing the Piedmont region of North Carolina, Gruber and colleagues (1981;1985) examined the effects of different types of residential arrangements and found that single-family dwellings and mobile home residents were more satisfied with their housing costs than were apartment residents. Mobile home residents were more satisfied than conventional home residents with the community amenities available where they lived.…”
Section: Tenurementioning
confidence: 99%